PENDIDIKAN BERBASIS KONSTRUKTIVISME DALAM MENINGKATKAN KEBERMAKNAAN BELAJAR DI ERA DIGITAL - Zahrotus Saidah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
Substantive meaningfulness is defined by the ability of students to be associated with relevant concepts contained in students' cognitive learning, resulting in fun learning, so that it can be achieved, and expressing information in its entirety, as well as having implications for increasing students' abilities in constructing new knowledge, thus producing results. The research aims to answer how the impact of implementing constructivism-based learning in the digital era questions in increasing the meaning of PAI learning to produce digitally. This research is qualitative research, using a case study approach. The primary sources used were documentation, in-depth interviews, and focus group discussions with students of SD Muhammadiyah 1 Alternative City Magelang. While the secondary sources used are books, papers, journals, magazines, articles, journals, websites, and so on, which are related to the research theme. From the results of the study, it can be said that learning is the key to student empowerment in the digital era. The results of this study prove that the meaningfulness of Islamic Religious Education learning for the digital generation can be increased through the application of digital-based constructivist learning methods.